2022
DOI: 10.3390/ani12243544
|View full text |Cite
|
Sign up to set email alerts
|

Beef Cattle Preference and Usage of Environmental Enrichments Provided Simultaneously in a Pasture-Based Environment

Abstract: Environmental enrichment can improve livestock welfare through increasing environmental complexity to promote a greater range of natural behaviours. However, there is limited understanding of the need for and impacts of enrichments for extensively managed beef cattle that can sometimes be kept in grassed paddocks devoid of additional natural and artificial features, i.e., ‘barren pastures’. This trial assessed which enrichments beef cattle preferred and utilised in a barren paddock environment. Eight groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The brush was used five to six times more than either the rope or ball, and the ball appeared to be the least favoured enrichment. Previous studies reported conflicting preferences between a brush and a hanging rope, with beef steers at pasture utilising a brush more (Dickson et al, 2022), weaned group-housed dairy calves preferring a rope (Strappini et al, 2021), and pair-housed dairy calves using both enrichments for similar total durations (Zobel et al, 2017). However, these differences might be due to the age of the calves as younger calves may have a stronger motivation to suckle and therefore utilise a rope allowing for oral manipulation.…”
Section: Pen Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…The brush was used five to six times more than either the rope or ball, and the ball appeared to be the least favoured enrichment. Previous studies reported conflicting preferences between a brush and a hanging rope, with beef steers at pasture utilising a brush more (Dickson et al, 2022), weaned group-housed dairy calves preferring a rope (Strappini et al, 2021), and pair-housed dairy calves using both enrichments for similar total durations (Zobel et al, 2017). However, these differences might be due to the age of the calves as younger calves may have a stronger motivation to suckle and therefore utilise a rope allowing for oral manipulation.…”
Section: Pen Behavioursmentioning
confidence: 99%
“…A photograph of each enrichment used is shown in Figure 1C. The brush was chosen as it is the preferred enrichment of beef steers (Dickson et al, 2022), the rope was chosen to potentially satisfy a suckling motivation of the young calves (De Passille, 2001;Zobel et al, 2017), and the ball was chosen to encourage play behaviour (Bulens et al, 2014).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation